PENGARUH AUDIT FEE, KONDISI PERUSAHAAN DAN PROFESIONALISME SERTA HUBUNGAN KLIEN DENGAN AKUNTAN TERHADAP PENDAPAT/OPINI AKUNTAN BERKAITAN DENGAN INDEPENDENSI STUDI PADA KANTOR AKUNTAN PUBLIK DI KOTA MALANG - Puspitosarie, Endah - (JURNAL MANAJEMEN DAN AKUNTANSI, 2012)
Abstrack: The purpose of this study was to determine whether there is overall  effect (simultaneous) or individual (partial) Audit fee, Condition of the Company and Professionalism) and Client Relations with the Accountant to the Opinion / Opinion Accountants  Relating to Independent Study in Public Accountant in the city of Malang. The method used to analyze the use of regression analysis.The results showed that there is influence of the simultaneous audit fee, the condition of the company and professionalism  and client relationship with the Accountant  on the Opinion/Opinion Accountant. Judging from the Ftest of the obtained results for the F count greater than Ftabel 1587.262 for 9.117 which means the independent variables affect the dependent variable Y (opinion accountants)simultaneously.  T-test results as follows: - thitung X1 (audit fees) of -11 796 and -3.182 TTable. – Thitung X2 (state enterprises) amounted to 13,762 and by 3182 TTable. - Thitung X3 (professional accountant) of 4.942 and 3.182 amounting to TTable. - Thitung X4 (client relationships) of 12.921 and a TTable by 3.182. From the t test analysis of the above it can be concluded that partially independent variables (X1, X2, X3, X4) have a significant effect on the dependent variable Y (accountant opinion). Key words: Audit fee, Condition of the Company, Professionalism and Client Relations with the Accountant, Opinion Accountants